Bacterial load of German cockroach (Blattella germanica) found in hospital environment. (April 2014) - Menasria, Taha; Moussa, Fatima; El-Hamza, Souad; Tine, Samir; Megri, Rochdi; Chenchouni, Haroun
Abstract : Background: Cockroaches are among the most common pests in public dwellings and health facilities. Their presence can raise safety concerns, especially as they maybe carriers of pathogenic organisms. Methods: This study was carried out to isolate and identify the bacterial flora from German cockroaches ( Blattella germanica ). Cockroaches collected by hand catches from two public hospital environments in Tebessa city (northeast Algeria) were screened for microbial load from their external surfaces and alimentary tract using standard bacterial protocols. Results: A total of 174 bacterial isolates were isolated from 39 German cockroach specimens. The most common and abundant bacterial species belonged to the Pseudomonas group (23.5%) and Serratia (13.2%). Pathogens like Staphylococcus aureus were also isolated, as well as opportunistic pathogens like Klebsiella species and food spoilage bacteria such as Enterobacter and Citrobacter species were isolated from both external surface and digestive tract of the insect. Generalized linear models (GLM) were performed to analyze the variation of abundances and occurrences of bacterial isolates harboured by B. germanica . The GLMs revealed that the main factors affecting variation of bacterial diversity and abundance were sex and hospital ( P < 0.001). Conclusion: The findings of this study suggest that German cockroach acts as reservoir and potential vector of some bacterial pathogens.